Diet of coastal filter feeders : impact of factors operating at different scales - Puccinelli, Eleonora (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Benthic filter feeders have a key functional role in the dynamics of coastal food web as an intermediate trophic level and bioengineers. A wide variety of factors, operating across multiple spatial scales (e.g. hydrographic regime, human activities), can affect the composition of the water column and thus the availability of food for benthic populations. Food availability in turn affects the growth, reproductive rates and survival of benthic organisms, and consequently, can influence the functioning of the entire ecosystem. This study aims to evaluate how various environmental factors may modify the diet of intertidal filter feeders living along the South African coast. Specifically, the effects of biogeography, upwelling, urbanization and freshwater input on the dietary regimes of five species of filter feeders (two mussel and three barnacle species) were investigated using fatty acid (FA) and stable isotope (SI) analyses.Strong interspecific differences were found among the five species considered. However, all species responded to factors operating at large (100s km) and meso (10s- 100s km) scales (i.e. biogeography and upwelling respectively). The barnacles exhibit habitat segregation and showed different FA and SI signatures from each other, while the two mussel species, an invasive and native species that co-occur in the same mussel beds, had partially overlapping diets. Differences in their diets were found only using FA analysis, while their SI signatures differed on only one occasion. This highlights the importance of using the appropriate tool, and ideally combined techniques, to investigate diets.FA and SI signatures of all species considered changed among the three biographical provinces (west, south and east coasts of South Africa) exhibiting similar patterns that reflect the two oceanographic regimes that characterize the coastline: the eutrophic Benguela Current on the west coast and the oligotrophic Agulhas Current on the other two coasts. Upwelling had a significant effect on FA and SI signatures, with stronger effects on the west coast than the south coast. The results indicate that benthic filter feeders at upwelling areas consumed a mix of coastal macroalgal detritus and phytoplankton, which was probably brought onshore during downwelling events. At smaller spatialscales and using repeated sampling, the influence of upwelling on the west coast was found to be pervasive, rather than discrete, so that it may be more appropriate to categorize upwelling by referring to upwelling centres and downstream areas. SI underlined a significant effect of urbanization on the diet of filter feeders with an enrichment in the Î´Â¹â µN being characteristic of anthropogenic effect. Although a large number of rivers characterize the South African coast, no distinct effect of freshwater input was found for either the SI or FA signatures of the filter feeders. This contrasts with earlier work on demersal species and suggests that freshwater input does not significantly affect food availability for intertidal filter feeders, and that other factors (e.g. hydrogeography) are more important in determining the diet of these populations. These results highlight that environmental and anthropogenic factors operating at different spatial and temporal scales have a profound effect on benthic ecosystems, and that they control the relationship between primary production and primary consumers in coastal areas. Above all, this work highlights the importance of understanding the spatial and temporal scales at which different factors affect feeding regimes, and their critical role in coastal food webs.
Keywords: Benthic animals -- Ecology -- South Africa; Benthic animals -- Nutrition